The Effect of Hydrotherapy on Lowering Blood Pressure among Hypertension - Lontoh, Jessyca Cindy; Pitoy, Frendy Fernando (Global Health Science Group, 2025)
Hypertension is a cardiovascular disease and a non-communicable disease that poses a significant health risk due to its high mortality rate. It can lead to various health complications, including stroke, aneurysm, heart failure, heart attack, and kidney damage. Complementary therapies, when utilized traditionally, can assist in the management of hypertension. Examples of such therapies include warm water hydrotherapy and other water-based treatments. This study aimed to determine the impact of warm water foot-soak hydrotherapy on reducing blood pressure in hypertensive patients within the Airmadidi Health Center working Area. This research is a quantitative study that utilizes a quasi-experimental method with an equivalent control group design. The research sample was obtained through a non-probability sampling technique, specifically purposive sampling, which resulted in 40 participants divided into 20 in the control group and 20 in the intervention group. The intervention group administered warm water foot-soak hydrotherapy for a period of six consecutive days, with each session lasting 30 minutes and the water maintained at a temperature of 40°C. The statistical analysis employed was a bivariate analysis with the Mann-Whitney test. The results showed a significant difference in blood pressure values before and after hydrotherapy, with p-value = 0.000 for systolic and p-value = 0.000 for diastolic. Furthermore, the data shows a difference in the mean value of systolic blood pressure between the control group and the treatment group of 41.05 mmHg. In comparison, diastolic blood pressure values show a difference in the mean value of 35.35 mmHg. It is hoped that the community, especially people with hypertension, can use warm water foot bath hydrotherapy as a complementary therapy that can be done independently to help reduce blood pressure.